Fuzzy System Based Routing in computer Networks - Alshaheen, Hisham Shaalan Saiwan (University of Thi-Qar Journal of Science, 2013)
This paper presented fuzzy system to solve the routing problem. The proposed method is used two different metrics; link delay and congestion level to make routing decision and to manage congestion control. The fuzzy system is decides the selection level of neighbor node. So, the selection level of each neighbor node can be determined. The routing system selects best neighbor node, that has less value of link delay and congestion level from source to till destination. In this paper a performance improvement of fuzzy system is presented by adding a congestion level to together with link delay. These two input will beconsidered in route selection decision using fuzzy logic.